1985
DOI: 10.3739/rikusui.46.287
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus excretion by some zoobenthos in a eutrophic freshwater lake and its temperature dependency.

Abstract: The phosphorus excretion rate and its temperature dependency were investigated experimentally in four dominant species of zoobenthos in eutrophic freshwater lakes in and Kaori YASUDA*

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
4
25
1
Order By: Relevance
“…from the Gulf of Mexico was 0.7 nmol N mg dry mass ¡1 h ¡1 at 20À23 C (Gardner et al 1993), which was comparable to the results in this study. Fukuhara and Yasuda (1985) reported the SRP excretion rate of 0.07 nmol P mg dry mass ¡1 h ¡1 for Limnodrilus at 15 C (incubation time 7 h), which was lower than the result in this study. The excretion rates by L. hoffmeisteri in this study (20 C) were lower than the results (at 22 C) reported by Devine and Vanni (2002).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…from the Gulf of Mexico was 0.7 nmol N mg dry mass ¡1 h ¡1 at 20À23 C (Gardner et al 1993), which was comparable to the results in this study. Fukuhara and Yasuda (1985) reported the SRP excretion rate of 0.07 nmol P mg dry mass ¡1 h ¡1 for Limnodrilus at 15 C (incubation time 7 h), which was lower than the result in this study. The excretion rates by L. hoffmeisteri in this study (20 C) were lower than the results (at 22 C) reported by Devine and Vanni (2002).…”
Section: Discussioncontrasting
confidence: 56%
“…Several studies have shown that the mass-specific excretion rate by macrozoobenthos depended on the incubation time and temperature. The nutrient excretion rate generally tended to increase with temperature, and decrease with incubation time (Bayne & Scullard 1977;Fukuhara & Yasuda 1985Gulati et al 1989;Devine & Vanni 2002). Moreover, the excretion rate in natural conditions might be affected by food availability and ingestion rates (Johannes 1964;Mather et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Waters 1977). # Fukuhara and Yasuda (1985) report data on P excretion, while Fukuhara and Yasuda (1989) report N excretion data, from the same study.…”
Section: áDmentioning
confidence: 99%
“…There was a positive dependence on temperature, but with regard to differences between the two types of invertebrates, the results were equivocal. Gardner and others (1981), Fukuhara and Yasuda (1985) and Fukuhara and Sakamoto (1987) measured higher excretion rates in chironomids, whereas Devine and Vanni (2002) measured higher excretion rates in tubificids.…”
Section: Possible Role Of Benthic Invertebrates In Internal Loading Imentioning
confidence: 99%